Immunogenicity and protective efficacy of a native Omp34 subunit vaccine against Aeromonas hydrophila in BALB/c mice: identification of nitroblue tetrazolium as a correlate of protection within a One Health framework - Rozi, Rozi; Tyasningsih, Wiwiek; Rahmahani, Jola; Aksono Herupradoto, Eduardus Bimo; Yunus, Muchammad; Anam Al Arif, Mohammad; Kuncorojakti, Suryo; Salleh, Annas; Suwarno, Suwarno (Veterinary World, 2025)
Background and Aim: Aeromonas hydrophila is a zoonotic, antimicrobial-resistant pathogen that causes significant losses in aquaculture and raises important One Health concerns. Outer membrane protein (OMP)-based subunit vaccines provide a targeted, antibiotic-sparing alternative to traditional bacterins, but validation across mammalian species remains limited. This study assessed the immunogenicity, safety, and protective effectiveness of a native ~34 kDa Omp34 (nOmp34) subunit vaccine in BALB/c mice, comparing it to a formalin-killed cell (FKC) vaccine, and examined immune factors that may predict survival. Materials and Methods: Female BALB/c mice (n = 13 per group) received subcutaneous injections of phosphate-buffered saline (PBS), FKC, FKC + incomplete Freund’s adjuvant (IFA), or native Omp34 + IFA on days 0, 14, and 28. Immune responses were assessed by measuring anti-Omp34 immunoglobulin (Ig)G2a levels via enzyme-linked immunosorbent assay, serum lysozyme activity, nitroblue tetrazolium (NBT) respiratory burst, and phagocytic activity at specified intervals up to day 42. On day 42, mice were challenged intraperitoneally with a lethal dose of A. hydrophila, causing 80% mortality, and observed for 14 days for survival, clinical scores, and body weight changes. Data analysis involved analysis of variance with Tukey post hoc tests, mixed-effects modeling, Spearman correlation, receiver operating characteristic curves, logistic regression, and Kaplan-Meier survival analysis. Results: By day 42, all immune biomarkers showed clear separation (nOmp34+IFA > FKC + IFA > PBS; p < 0.05). NBT demonstrated the strongest correlation with survival (ρ 0.90) and the highest predictive performance (Area under the curve [AUC] 0.80), exceeding IgG2a and phagocytosis (AUC 0.70). Post-challenge survival rates were 84.6% for nOmp34 + IFA, 61.5% for FKC + IFA, and 23.1% for PBS, corresponding to relative percent survival values of 80% and 50% compared to PBS. The direct comparison between nOmp34 and FKC revealed a favorable but not statistically significant survival benefit (p = 0.238). Vaccination was well-tolerated, with stable body weight, minimal reactogenicity, and no severe clinical events. Conclusion: The nOmp34 subunit vaccine elicited a strong, coordinated humoral and innate immune response, surpassing the matched bacterin in both efficacy and immune strength. NBT activity between days 35-42 proved to be a practical indicator of protection, aligning mechanistically with nicotinamide adenine dinucleotide phosphate -oxidase-mediated bacterial killing. These findings offer proof-of-concept for Omp34 as a scalable, antibiotic-sparing vaccine candidate and support its progression into aquaculture-relevant platforms within a One Health framework.